Velhice na cultura contemporânea - Pitanga, Danielle de Andrade (2006)
The scope of this research is to investigate the specific ways of getting old in the cultural context of nowadays. Taking in account that each individual gets old in an absolutely particular way, we can say that there are several forms of getting old and several kinds of old aged. The nowadays consume society, in a fast and frenetic way is marked by the culture of image. Body is super valorized and requested. Success and happiness imply in the acceptance of models printed in the narcisistic charm, beauty and youth. In the opposite side is the old age that, unavoidably, uses to prior negative attributes: decrepitude, nostalgia, degeneration, decline, obsolescence and improductivity. It is thus created a scenery that leads to the idea of rejection and fear to get old due to the myth of everlasting youth . Reflection over exacerbated narcisism and worship to the body, led me to think and question what would the position to old people be? Apparently, all leads to believe that is exactly the nowhere . The proposal is only to give a chance to these old people, i.e., give them a place , and, above all, the desire of giving them voice , by listening their speeches. To achieve this goal, six interviews were taken with old aged people of both sexes, over 60 years old, of medium class, all of them actives, keeping some kind of intellectual or physical activity. It is a theoretical-clinical research, of psychoanalytic inspiration, despite the most recent contributions of authors that deal with the matter of getting old and old aged, have importance to the discussion. The research has the character of clinical method, because the clinical fragments of some old aged attended by me in consultory and the answers were submitted to interpretation, serving them to illustrate the theory